VIOLATION OF GRICE’S COOPERATIVE PRINCIPLE ON THE DIALOGUE OF “THE WILD DUCK” BY HENRIK IBSEN - Mufidah Ulin Nur (Faculty of Education and Teachers Training, 2018)
Communication is important for people in society. Pragmatics offers Grice’s cooperative principle to make the conversational contribution such as is required, context based acceptable, and accepted purpose of the talk. Violation on Grice’s maxims can cause misunderstanding which makes conversation fail. It also happens on the dialogue of drama, which is a representation of human’s communication. The subjectives of this research are to know kinds of maxims violation and the dominant maxim violation found on the dialogue of “The Wild Duck” by Henrik Ibsen are. This research belongs to descriptive qualitative research. Furthermore, the technique of collecting data is documentation where the script of drama “The Wild Duck” by Henrik Ibsen as the basic data to be analized in term of violation of Grice’s cooperative principle. Then, to analyze the data, the writer uses Krippendorff (2004) content analysis. The result of this research shows there are 51 (100%) maxim violations. They are divided into 16 (31.37% ) violations of quantity maxim, 12 (23.53% ) violations of quality maxim, 12 (23.53%) violations of relation maxim, and 11 (21.57%) violation of manner maxim. Moreover, the dominant violation is quantity maxim with 16 (31.37%) violations of total findings.